2020
DOI: 10.3390/microorganisms8050765
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Purpose Inoculants and Their Effects on Corn Silage

Abstract: This study was conducted to screen dual-purpose lactic acid bacteria (LAB) from uncontrolled farm-scale silage, and then we confirmed their effects on corn silage. The LAB were isolated from eight farm-scale corn silages, and then we screened the antifungal activity against Fusarium graminearum and the carboxylesterase activity using spectrophotometer with p-nitrophenyl octanoate as substrate and McIlvane solution as buffer. From a total of 25 isolates, 5M2 and 6M1 isolates were selected as silage inoculants b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 30 publications
15
35
0
Order By: Relevance
“…Similar to the present study, several previous studies also reported the improvement of rumen digestibility by application of inoculant producing esterase [4,5]. TIn addition, the reason for the lower the fraction degradation rate in INO silages was unclear.…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 87%
See 3 more Smart Citations
“…Similar to the present study, several previous studies also reported the improvement of rumen digestibility by application of inoculant producing esterase [4,5]. TIn addition, the reason for the lower the fraction degradation rate in INO silages was unclear.…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 87%
“…The WCR before and after ensiling were sub-sampled at 500 g, respectively, to analyses chemical composition and in vitro digestibility. Also, 20 g of ensiled WCR was sub-sampled and blended with 200 mL of sterile ultrapure water for 30 sec, and then filtered through two layers of cheesecloth to make silage extraction [3][4][5]. The fresh silage extraction was used to analyze pH and microbial counts.…”
Section: Inoculant Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…The substrates and dried residues were analyzed for NDF [ 14 ] using an Ankom 200 Fiber Analyzer. Residue weights and NDF concentration were used to calculate in vitro DM digestibility (IVDMD) and in vitro NDF digestibility (IVNDFD), according to a previous study [ 15 ]. The supernatant filtered from the in vitro fermentation was used for pH, ammonia-N, and SCFA analyses.…”
Section: Methodsmentioning
confidence: 99%